2014
DOI: 10.1117/12.2056509
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years of Chandra operation: scientific highlights and lessons learned

Abstract: NASA's Chandra X-Ray Observatory, designed for three years of operation with a goal of five years, is now entering its 15-th year of operation. Thanks to its superb angular resolution, the Observatory continues to yield new and exciting results, many of which were totally unanticipated prior to launch. We discuss the current technical status, review some recent scientific highlights, indicate a few future directions, and present what we are the most important lessons learned from our experience of building and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We anticipate benefit from the early development of high-fidelity simulations as a tool to illuminate the tall poles in the error budget, guide the choices toward performance optimization, and enable strategic comparisons by providing an integrated end-to-end measure of the entire process. 25,26 Our Chandra experience has shown that multiple independent performance predictions are needed to inject sufficient discourse into the development process to have confidence that test results will satisfy requirements, 27,28,29 so we approach the problem by starting to develop a flexible set of tools, which are specific to the mounting and alignment problem and independent of other likely methods.…”
Section: System Level Approachmentioning
confidence: 99%
“…We anticipate benefit from the early development of high-fidelity simulations as a tool to illuminate the tall poles in the error budget, guide the choices toward performance optimization, and enable strategic comparisons by providing an integrated end-to-end measure of the entire process. 25,26 Our Chandra experience has shown that multiple independent performance predictions are needed to inject sufficient discourse into the development process to have confidence that test results will satisfy requirements, 27,28,29 so we approach the problem by starting to develop a flexible set of tools, which are specific to the mounting and alignment problem and independent of other likely methods.…”
Section: System Level Approachmentioning
confidence: 99%